2019
DOI: 10.7150/jca.29086
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of common variants in Interleukin 33 gene with susceptibility and prognosis of osteosarcoma in Han Chinese population

Abstract: Osteosarcoma (OS) is one of the most common malignant bone tumors. Many previous studies have indicated that OS is a complex disease and that its development may be affected by multiple genetic factors, which may contribute to its carcinogenesis. The aim of the present study was to evaluate the relationship of IL-33 with susceptibility and prognosis of OS in Han Chinese individuals. A total of 1,605 study subjects including 507 OS patients and 1,098 controls were recruited. Eighteen SNPs mapped to IL-33 were s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 39 publications
(41 reference statements)
0
5
0
Order By: Relevance
“…Also, IL-33 gene polymorphisms were reported to be correlated with an increased risk of osteosarcoma [19]. IL-33 has been identified as a potential risk factor for the development and prognosis of osteosarcoma [20]. However, the role of IL-33 in human osteosarcoma cells remains to be determined.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, IL-33 gene polymorphisms were reported to be correlated with an increased risk of osteosarcoma [19]. IL-33 has been identified as a potential risk factor for the development and prognosis of osteosarcoma [20]. However, the role of IL-33 in human osteosarcoma cells remains to be determined.…”
Section: Discussionmentioning
confidence: 99%
“…These findings indicate that IL-33 may promote tumor progression. However, although IL-33 has previously been reported to be expressed in osteosarcoma [18][19][20], the role and mechanisms of IL-33 in osteosarcoma cells remain unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Multiple SNPs were located within ATAC-Seq peaks in the 1A1-1B intron region that correspond to putative enhancers (dashed boxes, including rs72614080, rs16924159, rs16924161, and rs12551256). Among these, rs72614080 is associated with prognosis in osteosarcoma ( 45 ), rs16924159 with vascular disease ( 46 ), and an off-peak SNP rs1891385 with COPD ( 47 ). Other SNPs associated with airway disease ( 42 ) are located ~6 kb proximal to the A2 promoter (rs992969 and rs3939286) and do not correspond to ATAC-Seq peaks observed in this data set; however, an AP-1 binding site was reported within the region encompassing these SNPs.…”
Section: Resultsmentioning
confidence: 99%
“…Noteworthy, the TT genotype of this variant was not related to GLDC expression, but it was associated to lower expression of interleukin-33 (IL33) (40,76). On top of that, Kang and colleagues genotyped common variants in the IL33 gene and found that the A-allele of rs1048274 was associated to survival in a osteosarcoma patient cohort of Chinese ancestry (77). The patient cohort of Koster et al consisted of European and Brazilian subjects and they did not identify statistically signi cant associations with common variants in IL33.…”
Section: Discussionmentioning
confidence: 99%